Transesterification reaction optimization and evaluation of biodiesel produced from seed oil of Colocynthis citrullus L. - Giwa, Solomon O.; Abdullah, Luqman Chuah; Adam, Nor Mariah (American V - King Scientific Publishing, 2014)
This work presents Colocynthis citrullus L. (egusi) seed oil as a potential feedstock for biodiesel production. The transesterification process was optimized using response surface methodology (RSM) with three-level-three-factors face-centered central composite design employed. Catalyst (NaOH) amount (0.25-1.8％ (w/w), reaction temperature (45-65 °C) and oil-methanol molar ratio (4-10) were studied as important factors influencing the reaction. The optimum values (1:6.54 oil/methanol molar ratio, 1.22％ (w/w) catalyst amount, and 65 ºC reaction temperature) predicted by the mathematical model generated using RSM gave ester yield of 84.46％, under experimental conditions. The fuel properties of egusi oil methyl ester (EOME) measured satisfied both ASTM D6751 and EN 14214 biodiesel standards with a kinematic viscosity of 3.87 mm2/s. Fatty acid profile and fuel properties of EOME were found similar to those of soybean, safflower and sunflower biodiesel.